Epothilones: From Discovery to Clinical Trials - Forli, Stefano (Current Topics in Medicinal Chemistry, 2014)
Epothilones are natural compounds isolated from a myxobacterium at the beginning of the 1990s, and showed a remarkable anti-neoplastic activity. They act through the same mechanism of action of paclitaxel, by stabilizing microtubules and inducing apoptosis. Although, their chemical structure, simpler than taxanes, makes them more suitable for derivatization. Their interesting pharmacokinetic and bioavailabilty profiles, and the activity against paclitaxel-resistant cell lines make them interesting therapeutic agents. Here a brief historical perspective of epothilones is presented, since their isolation, the identification of their mechanism of action and activity, to the recent clinical trials.
Keywords: Tubulin